On the Stability of Nigeria's Import Demand: Do Endogenous Structural Breaks Matter? - Shuaibu, Mohammed Isa; Fatai, Basiru Oyeniran (Journal of Reviews on Global Economics, 2014)
In this paper, we reassess the traditional import demand function and an augmented version that includes volatility of external reserves and oil revenue inflows as explanatory variables. In each version, we examine the role of regime shifts on the stability of Nigeria's import demand function which has been ignored in previous studies. Our findings suggest the existence of a long-run relationship between import demand and its determinants. We also present evidence of one-way causality running from changes in relative prices, oil revenue inflows and volatility of international reserves to import demand in Nigeria. However, when structural breaks were introduced, bi-directional causality is observed; indicating the critical role of regime shifts in determining the stability of Nigeria's import demand. The results make a case for diversifying Nigeria's revenue inflows in a bid to dampen the effect of contemporaneous shocks that affect external reserve accumulation thereby weakening its import financing capacity.